2021
DOI: 10.1007/s10072-021-05422-9
|View full text |Cite
|
Sign up to set email alerts
|

The factitious/malingering continuum and its burden on public health costs: a review and experience in an Italian neurology setting

Abstract: Factitious disorder is classified as one of the five aspects of somatic symptom disorders. The fundamental element of factitious disorder is deception, i.e., pretending to have a medical or psychiatric disorder, but the enactment of deception is considered unconscious. Indeed, volition, i.e., the perception of deliberate deception, is blurred in patients presenting with factitious disorder. In the USA and the UK, factitious disorder has received constant media attention because of its forensic implications and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Factitious disorders are an important item on the differential diagnosis list but are often unrecognized and misdiagnosed. As the volitional aspect, i.e., perception of deliberate deception in affected patients is blurred, differentiation from functional, dissociative and somatoform disorders and simulation/aggravation is often challenging [ 3 , 41 ]. The absence of clear external incentives and a strong propensity to self-harm distinguish factitious disease from malingering [ 3 ].…”
Section: Discussion Of Casementioning
confidence: 99%
“…Factitious disorders are an important item on the differential diagnosis list but are often unrecognized and misdiagnosed. As the volitional aspect, i.e., perception of deliberate deception in affected patients is blurred, differentiation from functional, dissociative and somatoform disorders and simulation/aggravation is often challenging [ 3 , 41 ]. The absence of clear external incentives and a strong propensity to self-harm distinguish factitious disease from malingering [ 3 ].…”
Section: Discussion Of Casementioning
confidence: 99%
“…Several reviews quote the DSM-5 categorization (10), in which factitious disorders are placed in a separate category of somatic symptoms disorders (which, nonetheless, include FND). Many discussions on FND compare this disorder to Malingering (16,17), overlooking or ignoring the complex question posed by the imposing presence of Factitious Disorders.…”
Section: Overlaps Between Fnd and Neurological Disorders Likementioning
confidence: 99%
“…The boundaries between the various discussed disorders were therefore considered unclear and a possible continuum was suggested, and the "Hystero-malingering continuum" appears in the literature (10,16,17,48,67,98). For example, it was shown that hysteric patients misinterpret evidence and selectively attend to only a certain part of the overall evidence.…”
Section: Interpretations Of Fnd and Ssdmentioning
confidence: 99%
See 1 more Smart Citation